Effect of selective pruning cuts on the vegetative and reproductive growth and the nitrogen and carbohydrate reserves of Protea cv. Carnival - Greenfield, Elizabeth Joy (Stellenbosch : Stellenbosch University, 2012)
Thesis (MScAgric) -- University of Stellenbosch, 1994.